2017
DOI: 10.1021/acsami.7b01096
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Carbides-Based Nanocomposite as Superior Electrocatalyst for Oxygen Evolution Reaction

Abstract: The development of highly efficient and low-cost oxygen evolution electrocatalysts is extremely imperative for the new energy technology. Transition metal carbides have been investigated as remarkable hydrogen evolution reaction (HER) electrocatalysts but undesired oxygen evolution reaction (OER) electrocatalysts and need further study. Here, a cobalt-molybdenum-based bimetallic carbide coated by N-doped porous carbon and anchored on N-doped reduced graphene oxide film (CoMoC/NCRGO) is synthesized by directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 46 publications
(58 reference statements)
0
84
0
Order By: Relevance
“…Figure compares the OER performance of metal borides and borates with that of precious metal catalysts (RuO 2 , IrO 2 ) as well as best representatives from other family of nonprecious metal catalysts (phosphides, carbides, sulfides, nitrides). As the amount of catalyst governs the OER performance, we restrict to only those catalysts that use a loading < 3 mg cm −2 .…”
Section: Discussionmentioning
confidence: 99%
“…Figure compares the OER performance of metal borides and borates with that of precious metal catalysts (RuO 2 , IrO 2 ) as well as best representatives from other family of nonprecious metal catalysts (phosphides, carbides, sulfides, nitrides). As the amount of catalyst governs the OER performance, we restrict to only those catalysts that use a loading < 3 mg cm −2 .…”
Section: Discussionmentioning
confidence: 99%
“…X‐ray photoelectron spectroscopy (XPS) spectra revealed the existence of C, Co, O and B in BC/Co 3 O 4 (Figure ), which was in accordance with the results of ICP‐OES and elemental analyses. Three types of carbon species, with deconvoluted peaks located at 284.5, 285.5 and 289.0 eV, were assigned to C−C, C−O and C=O, respectively . The B 1s spectrum displayed a sharp peak at about 192 eV, corresponding to B‐C 2 O/B‐CO 2 species .…”
Section: Methodsmentioning
confidence: 99%
“…Three types of carbon species, with deconvoluted peaks located at 284.5, 285.5 and 289.0 eV,w ere assigned to CÀC, CÀ Oa nd C=O, respectively. [13] The B1 ss pectrum displayed a sharp peak at about 192 eV,c orresponding to B-C 2 O/B-CO 2 species. [8c] This indicated that most of boron might be located on carbon layers between the metal oxide NPs.…”
mentioning
confidence: 99%
“…Currently, some materials resulting from the carbonization of POM‐containing precursors have been tested as OER electrocatalysts. A cobalt‐molybdenum‐based bimetallic carbide coated by N‐doped porous carbon and anchored on N‐doped rGO film (Co 6 Mo 6 C 2 /NCRGO) was synthesized by directly carbonizing the Co‐doped polyoxometalate/conductive polymer/graphene oxide precursors (Figure ) . The resultant composite showed to be a robust OER electrocatalyst, displaying a low overpotential of η 10 =0.260 V vs. RHE, a small TS of 50 mV dec −1 and long‐term stability.…”
Section: Introductionmentioning
confidence: 99%